(untitled) (Tạp chí Y học Cộng đồng, 2026)
Introduction: Health education (HE) provided by pediatric nurses is a key intervention, given that Respiratory Syncytial Virus (RSV) constitutes a leading burden of disease in children. This study aims to describe the knowledge and practices of pediatric nurses regarding HE for RSV disease. Subjects and Methods: A cross-sectional descriptive study was conducted from 04/2025 to 10/2025 on 89 pediatric nurses at 7 hospitals within the Vinmec system. Results: The study sample possessed high professional qualifications (88.8% University/Postgraduate) and extensive experience (73.0% seniority > 5 years). 100% had received HE updates. The overall knowledge achievement rate was 61.8%, with a mean score of 22.7 ± 2.1; the "Disease prevention knowledge" domain had the lowest mean score (2.6 ± 0.6). The overall practice achievement rate was 61.8%, with a mean score of 50.2 ± 8.8. The skills "Listening" (4.7 ± 1.2) and "Encouraging" (4.6 ± 1.2) had the lowest mean scores. The Formal training group had a higher practice achievement rate (70.0%) than the Articulation (upgrading) group (44.8%). Conclusion: The achievement rates for both knowledge and practice of HE on RSV among nurses were 61.8%. Despite a strong professional background, the study identified gaps in prevention knowledge and the practice of deep communication skills. The Formal group practiced more effectively than the Articulation group, indicating the need for specialized and focused training programs.